Toward a Science of Business Administration - Simonds, Rollin H. (Academy of Management Journal, 1959)
Emphasizes the development and extension of the science portion of business administration. Criticism of business courses and business administration books; Factors involved in the internal and external aspects of business operations; Controversy over the principle of span of control in organization theory.